2021
DOI: 10.1007/s00167-021-06766-7
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient evidence to confirm benefits of custom partial knee arthroplasty: a systematic review

Abstract: Purpose The purpose of this systematic review was to synthesise the available literature and critically appraise current evidence on the functional and radiographic outcomes as well as reoperation and revision rates of custom partial knee arthroplasty, i.e., unicompartmental knee arthroplasty (UKA), bicompartmental knee arthroplasty (BKA), and patellofemoral arthroplasty (PFA). Material and methods This systematic review was performed in accordance with the guidelines of Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It did not demonstrate significant benefits in terms of knee and function scores or range of motion, and had higher early revision rates, although the latter were not statistically significant [ 33 ]. Demey et al also failed to find any advantages in favor of individualized implants in a meta-analysis for partial joint replacement [ 34 ]. Higher rates of malpositioning, overcorrection, or loosening were also shown in one study each on TKA, bicompartmental knee arthroplasty (BKA), and unicondylar knee arthroplasty (UKA) [ 35 , 36 , 37 ].…”
Section: Knee Arthroplastymentioning
confidence: 99%
“…It did not demonstrate significant benefits in terms of knee and function scores or range of motion, and had higher early revision rates, although the latter were not statistically significant [ 33 ]. Demey et al also failed to find any advantages in favor of individualized implants in a meta-analysis for partial joint replacement [ 34 ]. Higher rates of malpositioning, overcorrection, or loosening were also shown in one study each on TKA, bicompartmental knee arthroplasty (BKA), and unicondylar knee arthroplasty (UKA) [ 35 , 36 , 37 ].…”
Section: Knee Arthroplastymentioning
confidence: 99%
“…However, BiKA may result in a slightly better post-operative range of motion (ROM) and less intraoperative blood loss [ 12 , 15 ]. Despite the available research, it is still challenging to determine the advantages and disadvantages of partial knee arthroplasty due to the limited number of studies utilizing robot-assisted technology to perform partial knee replacements and inconsistent reported outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted comparing TKA and partial knee replacements [7][8][9][10][11][12][13][14][15][16][17][18][19]. The research has found that UKA can lead to improved functional outcomes, but with higher revision rates [9], although some patients report less pain [17] and greater satisfaction [20,21].…”
mentioning
confidence: 99%
“…However, BiKA may result in slightly better post-operative range of motion (ROM) and less intraoperative blood loss [12,15]. Despite the available research, it is still challenging to determine the advantages and disadvantages of partial knee arthroplasty due to the limited number of studies utilizing robot-assisted technology to perform partial knee replacements and inconsistent reported outcomes [10].…”
mentioning
confidence: 99%